Implementasi Delay Tolerant Network (DTN) dengan Menggunakan Algoritme Hierarchical Token Bucket untuk Seleksi Node Routing Multicopy - Hidayatus Syafa'ah; Rakhmadhany Primananda; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Delay Tolerant Network is network used for long distatnce communication with layer addition, whic is bundle layer. In Delay Tolerant Netwrok, routing becomes a challenge in its implementation. It is caused by the use of limited bandwidth and buffer thus it need bandwidth management in order to arranged overload in buffer using Hierarchical Token Bucket Algorithm. Routing is used to route messages from the source node to the destination node. There are two categories of routing protocols based on the number of message copies, namely singlecopy routing and multi routing copy. Multi copy routing is, the message will be forwarded to each node on the specified path. This routing is able to improve network performance in maximizing the delivery message and minimum delay. Hierarchical Token Bucket Algorithm used to control the use of bandwidth towards link given to client and limit the download and upload conducted by client. In this research, Hierarchical Token Bucket Algorithm implemented by using ONE Simulator simulation and JAVA programming languange in Eclipse. The result of test then analysed by using average latency, overhead ratio, delivery probabilty and average hop count parameter with scenario number of node 50, 100, 150 and 200 node and node speed 20-160km/hourand message size of 1MB. From the result of test, it is obtained that the implementation of Hierarchical Token Bucket Algorithm for node routing multi copy selection runs appropriaately due to it implements message delivery schedule based on ceil and rate parameter. It can be seen from the result of parameter test of overhead ratio for 15.9737ms, score of delivery probabilty for 0.9504%, score average hop count score is 20.5900ms and average latency score is 220.2333ms.